The world in our time : a memoir - Raychaudhuri, Tapan (Noida : HarperCollins Publishers India, a joint venture with the India Today Group, 2011)
Autobiography of a professor, and social scientist from India, now resident of the United Kingdom.
Keywords: Raychaudhuri, Tapan; College teachers -- India -- Biography; Social reformers -- India -- Biography; Intellectuals -- India -- Biography; Education